Strategy Used by English Department Students of Universitas Negeri Padang in the Process of Translating Cultural Term From English into Bahasa Indonesia - Rahfi Andika Wendra; Havid Ardi (Journal of English Language Teaching, 2021)
This study analyzes the translation process in translating cultural text and strategy in translating cultural terms made by the students in the academic year 2018 at the English Language and Literature Department. The purpose of this research is to identify the translation process done by students when translating cultural text entitled “The second funeral” and how is strategy used when students face cultural terms. This study was descriptive qualitative research used in analyzing the process and the strategy in translating cultural terms on the text. The instrumentation of this research was translation activity. In the process of translation, 2 students did one line translation and one student did circle translation. The translation strategies were found as follows: Using Google translate (81%) from 39 number of data, check dictionary (6%) from 3 number of data, and eliminated cultural term (13%) from 6 number of data The results of this study indicate that English Language and Literature Department students use Google translate as a strategy mostly used to translate cultural text entitled "The second funeral".